The impact of board size on firm performance: evidence from the UK - Guest, Paul M. (Taylor & Francis, 2009)
We examine the impact of board size on firm performance for a large sample of 2746 UK listed firms over 1981-2002. The UK provides an interesting institutional setting, because UK boards play a weak monitoring role and therefore any negative effect of large board size is likely to reflect the malfunction of the board's advisory rather than monitoring role. We find that board size has a strong negative impact on profitability, Tobin's Q and share returns. This result is robust across econometric models that control for different types of endogeneity. We find no evidence that firm characteristics that determine board size in the UK lead to a more positive board size-firm performance relation. In contrast, we find that the negative relation is strongest for large firms, which tend to have larger boards. Overall, our evidence supports the argument that problems of poor communication and decision-making undermine the effectiveness of large boards.
Keywords: Corporate governance; Board size; Firm performance; Endogeneity; UK